2020
DOI: 10.1186/s12872-020-01777-7
|View full text |Cite
|
Sign up to set email alerts
|

Addition of routine blood biomarkers to TIMI risk score improves predictive performance of 1-year mortality in patients with ST-segment elevation myocardial infarction

Abstract: Background Several biomarkers have been proposed as independent predictors of poor outcomes in ST-segment elevation myocardial infarction (STEMI). We investigated whether adding information obtained from routine blood tests including hypoxic liver injury (HLI), dysglycemia, anemia, and high neutrophil to lymphocyte ratio (NLR) could improve the prognostic performance of the TIMI risk score for the prediction of 1-year mortality. Methods A total of 1057 patients with STEMI undergoing primary percutaneous coron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The Oh PC study suggests that NLR can be used to indicate the severity of myocardial injury and whether there is adverse cardiac remodeling. In STEMI patients, high NLR is independently associated with the risk of death at 1 year after PCI 6 . Related studies have shown that NLR can not only predict the long-term mortality of patients with acute ST-segment elevation myocardial infarction 7 , but also reflect the severity of coronary artery disease, and is related to the SYNTAX score and Gensini score 8 .…”
Section: Introductionmentioning
confidence: 96%
“…The Oh PC study suggests that NLR can be used to indicate the severity of myocardial injury and whether there is adverse cardiac remodeling. In STEMI patients, high NLR is independently associated with the risk of death at 1 year after PCI 6 . Related studies have shown that NLR can not only predict the long-term mortality of patients with acute ST-segment elevation myocardial infarction 7 , but also reflect the severity of coronary artery disease, and is related to the SYNTAX score and Gensini score 8 .…”
Section: Introductionmentioning
confidence: 96%
“… 6 Although Niu et al 21 developed a risk stratification tree model using white blood cell count, hemoglobin, and mean platelet volume, it did not include the NLR. Recently, Oh et al 22 analyzed 1,057 patients with STEMI and demonstrated that the addition of elevated serum transaminase, dysglycemia, anemia, and high NLR improved the prognostic performance of the TIMI risk score for the prediction of 1-year mortality. Previously verified predictors in the early risk stratification for STEMI include not only the indicators of health status or CAD severity, such as older age, renal insufficiency, and previous angina or MI, but also hemodynamic parameters, such as low blood pressure, elevated heart rate, and high Killip class at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for an MACE included any of the following: acute myocardial infarction (AMI), PCI, CABG, and all-cause death. AMI was defined according to the fourth universal definition of MI ( 8 ), PCI was defined as any therapeutic catheter intervention in the coronary arteries, and CABG was defined as any cardiac surgery in which coronary arteries were operated on.…”
Section: Methodsmentioning
confidence: 99%
“…Guidelines suggest using risk scores in the ED for early stratification of patients with acute ischemic chest pain and selecting different treatment strategies for different prognoses (2). Several risk scoring systems, such as the thrombolysis in myocardial infarction (TIMI), the Global Registry of Acute Coronary Events (GRACE), HEART, Sanchis, and Florence scores, have been developed to aid in the risk stratification of patients with suspected or diagnosed ACS (3)(4)(5)(6)(7)(8). The TIMI and GRACE scores were developed for patients with ACS, the HEART score was developed for patients with the suspected ACS, the Sanchis score was developed for patients with chest pain, non-ST segment deviation ECG and normal troponin levels (5), and the Florence score was developed for patients with acute chest pain without known coronary artery disease (CAD) and with normal ECG and troponin levels (7).…”
Section: Introductionmentioning
confidence: 99%